Analisis Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Kosmetik - Husni, M. Fahrul (Movere Journal, 2024)
The cosmetics industry is one of the fast-growing sectors around the world, including Indonesia. Product quality and price are two main factors that influence consumer purchasing decisions. The study aims to analyze the impact of product quality and price on the decision to buy cosmetic products in Indonesia. The research method used is quantitative by collecting data through surveys to consumers of cosmetic products. Therefore, companies in the cosmetics industry should strive to improve product quality and establish appropriate pricing strategies to improve consumer purchasing decisions and increase market share.